Prevention of Hypertension at Intubation: A Controlled Study of Sublingual Nifedipine - Gyawali, Nirmal Kumar (Europasian Journal of Medical Sciences, 2020)
Background: Hypertension and tachycardia-induced after laryngoscopy and intubation can be prevented by various methods like deep inhalation anesthesia, intravenous opioids, topical intravenous lidocaine, intravenous adrenergic blocking drugs and pretreatment with antihypertensive. Methods: It is a randomized controlled double-blind prospective study of two groups consisting of 30 patients in each group. Group A was the control group and group B were Nifedipine group who were pretreated with Nifedipine. This study aimed to assess the effectiveness of pretreatment with nifedipine in the prevention of the hypertensive response to laryngoscopy and endotracheal intubation in normotensive patients undergoing elective surgery. Result: Sublingual nifedipine was significantly effective in decreasing systolic and diastolic blood pressure produced by laryngoscopy and tracheal intubation, but its role in decreasing pulse rate was not significant. Conclusion: Nifedipine is useful to prevent laryngoscopy and intubation induced hemodynamic response. DOI: https://doi.org/10.46405/ejms.v2i1.33